Suitability Analysis and Comparison of Rice Bran, Mustered and Blended Oils for High Voltage Applications - Brahmin, Anil; Neema, D.D; Dwivedi, Arpan; Bhonsel, Devanand (International Journal of Computer Sciences and Engineering, 2018)
In high voltage applications, the liquid insulating oils are used as the insulating medium as well as cooling medium. For the past several decades, the mineral based transformer oil which are extracted from petroleum crude oil is used traditionally for the purpose of liquid insulations. In the environmental aspect, there are several disadvantages of the mineral oil even though it has better insulating properties. By considering the environmental aspect and insulating properties, the researchers tend to find the alternate insulating fluids for the high voltage applications. Increasing power demand forces the development of the high-rated power devices such as Transformers Circuit Breakers etc. In a transformer, petroleum-based mineral oil is used as insulation, currently Transformer oil produces environmental and health issues because it is nonbiodegradable. Thus it has been thought that why not to use vegetable oils if found suitable. The present work investigates breakdown voltage, flash point & fire point of Three different vegetable oils namely Rice Bran (Hareli Brand), Mustered (Fortune Brand) and Blended (75%Rice Bran+25%Mustered) oils. Results obtained from experiments are validated with benchmark results and are found to be in good agreement as per IS-335:1993. The results are reported in dimensional form and presented graphically. The results provide a substantial insight in understanding the behavior of vegetable oil for high voltage applications. The Cost comparison of these oils with standard mineral oil is also tabulated.